1967
DOI: 10.1139/v67-160
|View full text |Cite
|
Sign up to set email alerts
|

Acetylenic esters. II. Further addition reactions with sulfur- and nitrogen-containing compounds

Abstract: Substituted thiosemicarbazides react with dimethyl acetylenedicarboxylate to give 3-amino-2,3-dihydrothiazin-4-ones. Confirmation of the structures is provided by catalytic hydrogenation and by characteristic mass spectral fragmentations. 4-Substituted thiosemicarbazides react with methyl propiolate in the same way as monosubstituted hydrazines and hydrazides to give hydrazones, whereas I-substituted thiosemicarbazides undergo smooth removal of the sulfur with the production of an equal mixture of cis-trans an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Lown et al , reported that, methyl 4‐oxo‐2‐phenyl‐4 H ‐1,3‐thiazine‐6‐carboxylate ( 191 ) was obtained by the reaction of N ‐methyl benzothioamide ( 190 ) with DMAD ( 1a ) in methanol at room temperature (Scheme ).…”
Section: Chemistry Of Dimethyl Acetylenedicarboxylatementioning
confidence: 99%
See 1 more Smart Citation
“…Lown et al , reported that, methyl 4‐oxo‐2‐phenyl‐4 H ‐1,3‐thiazine‐6‐carboxylate ( 191 ) was obtained by the reaction of N ‐methyl benzothioamide ( 190 ) with DMAD ( 1a ) in methanol at room temperature (Scheme ).…”
Section: Chemistry Of Dimethyl Acetylenedicarboxylatementioning
confidence: 99%
“…On the other hand, dimethyl 2‐[6‐(methoxycarbonyl)‐4‐oxo‐3,4‐dihydro‐2 H ‐1,3‐thiazin‐2‐ylimino]‐1,3‐dithiole‐4,5‐dicarboxylate ( 197a ) and ( E )‐dimethyl 2‐[6‐(methoxycarbonyl)‐4‐oxo‐3,4‐dihydro‐2 H ‐1,3‐thiazin‐2‐ylimino]‐3‐phenyl‐2,3‐dihydrothiazole‐4,5‐dicarboxylate ( 197b ) were formed via interactions between 5‐amino‐3 H ‐1,2,4‐dithiazole‐3‐thione ( 196a ) or 3‐(phenyl imino)‐3 H ‐1,2,4‐dithiazol‐5‐amine ( 196b ) and DMAD ( 1a ) in methanol at room temperature (Scheme ) .…”
Section: Chemistry Of Dimethyl Acetylenedicarboxylatementioning
confidence: 99%
“…The structure of the title compound was first reported by Ichikawa & Iitaka (1968 acetylenedicarboxylate (DMAD) have been given both the imidazolidin-4-one structure (1) (Sasaki, Sakata & Iwanami, 1964) and the pyrimid-4-one structure (2) (Ruhemann & Stapleton, 1900), although the structural assignments were often unsupported. Some chemical degradative evidence favours the fivemembered-ring structure (3) for the adduct from guanidine itself and DMAD (Katner & Zeige, 1971) but, in contrast, the adduct from 1,2,3-triphenylguanidine has been assigned the six-membered-ring structure (4), principally from its high-resolution mass (-c9 1980 International Union of Crystallography C24HI9N303 spectrum (Lown & Ma, 1967). The crystal structure of the adduct from 1,2,3-triphenylguanidine was therefore examined to gain some unambiguous information in this confused area.…”
Section: (2'mentioning
confidence: 99%
“…The adduct was prepared in 71% yield from c(32) 1,2,3-triphenylguanidine and DMAD in methanol c(33) (Lown & Ma, 1967) (7) 0.2858 (5) 0.3328 (3) 7.1 0.5570 (7) 0.2553 (6) 0.3635 (2) 6.6 0.4751 (7) 0.1897 (6) Tables 2 and 3. The product from 1,2,3-triphenylguanidine and DMAD has in fact the five-membered ring structure (5) (Fig.…”
Section: (2'mentioning
confidence: 99%
“…Reactions of thioamides with activated acetylenes normally involve the sulfur and nitrogen atoms and give rise to substituted 1,3-thiazolines [1,2] and 1,3thiazines [3,4]. It is also known that reactions of thioamides with acetylenedicarboxylic acid and its esters in benzene and acetonitrile form substituted 1,3thiazolin-4-ones [3,4].…”
mentioning
confidence: 99%